Patterns of dualisation: coordinated capitalism and the politics of flexible labour markets in Germany and Japan, 1990-2010 - Heinrich, Steffen (2013)
This study analyses the politics of labour market reforms in Germany and Japan in the period between 1990 and 2010. Unlike conventional policy studies which tend to focus solely on legislative politics, this study assesses cases of reform and non-reform in the context of industrial relations and corporate consultation practices. Acknowledging the multi-dimensional nature of labour market regulation helps to explain not only why some reforms are implemented but also the timing and scope of legislative reforms. Theoretically, the approach combines the insights of public policy and political economy literatures. The analyses cover several areas of labour market policy, i.e. temp agency work, fixed-term employment, working time, employment protection and minimum working conditions. The findings suggest that the institutions commonly associated with non-liberal capitalism possess considerable political clout as they can amplify, antedate, or mediate legislative reforms. Moreover, they can be used strategically by policy-makers to manage the salience of labour market policies, e.g. blame avoidance strategies. This also explains why reform processes frequently defy standard explanatory models of political reform such as veto player or partisan theory. Also, the institutional framework in the German and Japanese labour market arrangements also explaing why both countries are characterised by a strong labour market dualism which includes a dualisation of jobs, regulation and firm practices.
Online publiziert: 2014
Keywords: 1990-2010; Deutschland; Japan; Hochschulschrift